2012
DOI: 10.3892/mmr.2012.951
|View full text |Cite
|
Sign up to set email alerts
|

βig-h3 supports gastric cancer cell adhesion, migration and proliferation in peritoneal carcinomatosis

Abstract: Abstract. βig-h3 is an extracellular matrix protein and its expression is highly induced by transforming growth factor (TGF-β). It has also been suggested to play an important role in the growth and invasion of colon and pancreatic cancers. In the present study, we demonstrated that βig-h3 is expressed in mesothelial cells, especially in patients with advanced gastric cancer. The positive rate of βig-h3 was significantly higher in cases with a more invasive and advanced serous-type, with visible peritoneal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Lastly, beta ig-h3 is an adhesion molecule expressed on mesothelial cells. Upregulation is associated with increased in vitro gastric cancer cell adhesion and the presence of PM [ 142 ], suggesting a role for this molecule in PM. Furthermore, in an in vitro ovarian cancer model, peritoneal cells—but not tumour cells—showed high beta ig-h3 levels.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, beta ig-h3 is an adhesion molecule expressed on mesothelial cells. Upregulation is associated with increased in vitro gastric cancer cell adhesion and the presence of PM [ 142 ], suggesting a role for this molecule in PM. Furthermore, in an in vitro ovarian cancer model, peritoneal cells—but not tumour cells—showed high beta ig-h3 levels.…”
Section: Resultsmentioning
confidence: 99%
“…PLF yields information about the status of the peritoneum, such as changes in the population of immune cells and secretion of growth factors and cytokines [ 32 , 33 ]. Cytology and molecular diagnostic assays are based on the detection of cancer cells, whereas profiling of miRNAs in PLF may be used for the prediction of a peritoneal premetastatic phenotype in GC, ensuring more effective preventive and curative measures.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of BIGH3 on adhesion differs between cell types, possibly because it depends on the expression of BIGH3 or other adhesion proteins by the cells. Coating the cell culture surface with BIGH3 results in increased adhesion for most cells; 18,[38][39][40][41][42][43] however, decreased adhesion of melanoma and endothelial cells to BIGH3-coated surfaces is seen, possibly due to their high expression of endogenous BIGH3. 21,44 In our study, primary HSPCs showed adhesion to BIGH3-coated surfaces, at least in part via interaction with integrins on these cells.…”
Section: Discussionmentioning
confidence: 99%